Risco e preocupação com quedas em pacientes com diabetes Mellitus Tipo 2 - SOUSA, Sara Maria Ferreira de (2022)
Introduction: Episodes of falls are considered an important public health problem. Falls occur due to multifactorial circumstances, with internal and external (environmental) risk factors, being frequent in patients with Diabetes mellitus. Objective: To assess the risk of falls and concerns about falls in patients with Type 2 Diabetes Mellitus. Methodology: Cross-sectional study with a quantitative approach. Data collection took place at the Center for Medical Specialties and Diagnosis - PAM DIAMANTE, from August 2021 to June 2022, with patients with type 2 Diabetes mellitus in outpatient care, through a questionnaire to characterize the sociodemographic and clinical aspects . The risk of falling was assessed using the Downton Falls Scale and the concern about falls using the International Falls Effectiveness Scale - Brazil. This study is part of a larger project entitled Health Care Complexity in the Hospital and Outpatient Environment. Results: 373 patients participated in the study, 68.4% men and 31.6% women, with a mean age of 60.2 years. 89.1% of the patients had a high risk of falls, 53.6% reported the occurrence of falls after the diagnosis of diabetes, and in brown patients there were more reports of falls (42%), as well as in married or married patients. in a stable relationship (58.9%). The main concerns with falls were when performing the following activities: walking on a slippery surface (14.8%), going up or down a slope (9.8%) and going up or down stairs (8.5%). Conclusion: Patients with type 2 diabetes mellitus are at high risk of falls. The concern with falls was mentioned mainly in relation to environmental risks and for most activities of daily living, patients reported confidence in performing them. Most patients reported falls after the diagnosis of diabetes, which leads us to emphasize the importance of evaluating the risk of falls early in the course of the evolution of this pathology, aiming at the implementation of individualized strategies to prevent falls and, consequently, their complications.